Effectiveness of a clinical knowledge support system for reducing diagnostic errors in outpatient care in Japan: A retrospective study. (January 2018) - Shimizu, Taro; Nemoto, Takaaki; Tokuda, Yasuharu
Highlights: A single center, retrospective study for clinical effectiveness of a computer based system to reduce diagnostic error was performed. Diagnostic error rate of the computer-based system-equipped physicians was significantly lower than that of non-equipped physicians. Further validation with prospective, multicenter study will be needed for the wide clinical application of this study result. Abstract: Clinical evidence has indicated the effectiveness of computer-based systems for preventing and reducing diagnostic errors. Our study aimed to evaluate the effectiveness of UpToDate, a computer-based clinical knowledge management system, for reducing diagnostic errors. We retrospectively identified 100 patients who visited an outpatient department in a community-based hospital from July 2014 to June 2015. Fifty patients (exposure group) were seen by UpToDate-equipped physicians and another 50 (control group) were seen by UpToDate-unequipped physicians. We extracted data on patient sex, age, primary diagnosis, and case difficulty that could potentially affect diagnostic outcomes. We compared the two groups regarding diagnostic error rate and performed logistic regression analysis to analyze the concurrent effects of various factors affecting diagnostic error. The diagnostic error rate was 2% in the exposure group, while the error rate was 24% in the control group. Multivariate logistic regression analysis showed that error rate reduction was significantly associated with exposure to UpToDate with an odds ratio of 15.21 (95% CI 1.86–124.36). Our results demonstrated the effectiveness of UpToDate for the prevention and reduction of diagnostic error.